The role of γδ T17 cells in cardiovascular disease. Issue 6 (8th September 2022) - Ling, Shaoxue; You, Zonghao; Li, Yang; Zhang, Jian; Zhao, Shuwu; He, Yongzhi; Chen, Xi
Abstract: Due to the ability of γδ T cells to bridge adaptive and innate immunity, γδ T cells can respond to a variety of molecular cues and acquire the ability to induce a variety of cytokines such as IL-17 family, IFN-γ, IL-4, and IL-10. IL-17 + γδ T cells (γδ T17 cells) populations have recently received considerable interest as they are the major early source of IL-17A in many immune response models. However, the exact mechanism of γδ T17 cells is still poorly understood, especially in the context of cardiovascular disease (CVD). CVD is the leading cause of death in the world, and it tends to be younger. Here, we offer a review of the cardiovascular inflammatory and immune functions of γδ T17 cells in order to understand their role in CVD, which may be the key to developing new clinical applications. Graphical Abstract: This review provides a more comprehensive understanding of the biology of γδ cells and their role in CVD.